SYNTHESIS AND CHARACTERIZATION OF POLY(VINYLIDENE FLUORIDE) COPOLYMER NANOFIBER MODIFIED POLYVINYL ALCOHOL FOR ADSORPTION OF Cd(II) IONS - AFRIANINGSIH ( NIM : 20514040), IRLIN
Cadmium is a heavy metal that is widely used as a product in several industries such as Ni-Cd battery, electroplating, pigment and plastics industry. Pollution caused by the presence of Cd metal waste is very dangerous for the environment because it is toxic. If it accumulates in the human body, it can cause damage to the lungs, liver, kidneys, prostate and bladder. Therefore we need a method to remove the Cd metal from the waste. Adsorption is a method that widely used to remove heavy metal ions because it is an economical efficient method and requires non-organic solvents. Some materials have been developed as an adsorbent, one of them is the nanofiber material that synthesized by the electrospinning technique. The adsorbent material used in this research is nanofiber material that synthesized from PVDF copolymer. PVDF copolymer nanofiber has a hydrophobic nature and it is difficult to be used in adsorption of Cd metal. There is away to enhance the hydrophilic nature from this nanofiber that called the nanofiber surface modification. The modifications is done by coating the surface of the PVDF copolymer nanofiber using polyvinyl alcohol (PVDF-c-PVA). The optimum conditions of electrospinning process in synthesis of PVDF copolymer nanofiber are at the concentration of 20% (b/v), voltage 20 kV, the flow rate of 0.04 mL/min, and a nozzle-collector distance of 15 cm. The PVDF copolymer nanofiber are characterized using FTIR, SEM-EDS, XRD, BET and TEM. The results show some differences in nanofibers before andafter the surface modification. The differences are the spectrum shifts caused by the vibration of -OH derived functional groups from PVA, the morphologies, the percentages of crystalline and amorphous structures, the average diameter sizes and surface areas. Before the surface modifications is done, the morphology is in straight form and does not contain beads. The nanofiber has average diameter size which is about 396.50 nm, the surface area about 693.37 m²/g and the percentage of crystalline and amorphous structure which is about 68.70% and 31.30% respectively. After the modification is done, the morphology of (PVDF-c-PVA) nanofiber become misaligned and irregular. The nanofiber has the average diameter size which is about 505.50 nm, the surface area of 1987.65 m²/g and the percentageof crystalline and amorphous structures which is about 54.20% and 45.80% respectively. Optimization of adsorption is done through a batch method by evaluating the solution pH, contact time, initial dye concentration, and adsorbent dosage.The test results showed the optimum condition of adsorption of Cd(II) ions occurs at pH 4 and a contact time of 120 minutes, with a maximum adsorption capacity which is about 16.38 mg/g. Effect of the interfering ions were done with the batch method using ion Cd(II), Zn(II), Cu(II) and Pb(II) which shows that the (PVDF-c-PVA) nanofiber absorbent is not selective. The process of adsorption of Cd(II) by a (PVDF-c-PVA) nanofiber followed Langmuir adsorption isotherm and adsorption kinetics pseudo second-order.